Targeting Tumor Metabolism: A New Challenge to Improve Immunotherapy - Kouidhi, Soumaya; Ben Ayed, Farhat; Benammar Elgaaied, Amel (Frontiers in Immunology, 2018)
Abstract Currently, a marked number of clinical trials on cancer treatment have revealed the success of immunomodulatory therapies based on immune checkpoint inhibitors that activate tumor-specific T cells. However, the therapeutic efficacy of cancer immunotherapies is only restricted to a small fraction of patients. A deeper understanding of key mechanisms generating an immunosuppressive tumor microenvironment remains a major challenge for more effective anti-tumor immunity. There is a growing evidence that the tumor microenvironment supports inappropriate metabolic reprogramming that dampens T cell function, and therefore impacts the anti-tumor immune response and tumor progression. Notably, the immunosuppressive TME is characterized by a lack of crucial carbon sources critical for T cell function and increased inhibitory signals. Here, we summarize the basics of intrinsic and extrinsic metabolic remodelling and metabolic checkpoints underlying the competition between cancer and infiltrating immune cells for nutrients and metabolites. Intriguingly, the upregulation of tumor PD-L1 and CTLA-4 alters the metabolic programme of T cells and drives their exhaustion. In this context, targeting both tumor and T cell metabolism can beneficially enhance or temper immunity in an inhospitable microenvironment and markedly improve the success of immunotherapies.